Carbon nanocage packaged metal nanoparticle catalytic electrode, preparation method thereof and application of carbon nanocage packaged metal nanoparticle catalytic electrode in electro-catalysis nitrate reduction
By encapsulating metal nanoparticles in a hydrophilic layered carbon nanocage, the problem of competitive hydrogen evolution reaction in electrocatalytic nitrate reduction is solved, and high-efficiency ammonia synthesis in neutral electrolytes is achieved, with high Faraday efficiency and stability.
Patent Information
- Application Number
- CN202411772739.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has problems with competitive hydrogen evolution reactions (HER) in electrocatalytic nitrate reduction, and the lack of efficient catalysts in neutral/near neutral electrolytes, resulting in low ammonia synthesis efficiency.
By encapsulating metal nanoparticles in hydrophilic layered carbon nanocages, a carbon nanocage encapsulated metal nanoparticles composite catalyst with a closed or semi-enclosed structure is constructed and supported on a glass carbon electrode for electrocatalytic nitrate reduction.
The catalyst can exhibit excellent NO3RR activity in the neutral electrolyte, with a Faraday efficiency of more than 80%, a total current density of ammonia produced exceeds 80mAcm-2, and has high stability, avoiding loss and aggregation of metal nanoparticles.
Smart Images

Figure CN119710775A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a carbon nano cage encapsulated metal nano particle catalytic electrode and a preparation method thereof and application in electrocatalytic nitrate reduction. Background Art
[0002] Ammonia (NH3) is one of the most important building blocks in the world, widely used in the chemical and fertilizer industries, and is also a promising energy carrier in the hydrogen economy. The Haber-Bosch process for ammonia synthesis is energy-intensive, carbon-intensive, and capital-intensive, accounting for approximately 1% to 2% of global energy consumption, and is poorly compatible with distributed agriculture. Ammonia synthesis via electrocatalytic nitrogen reduction reaction driven by renewable electricity is a potential alternative to the Haber-Bosch process. However, the strong N≡N bonding in nitrogen and its low solubility in electrolytes make ammonia production thermodynamically and kinetically unfavorable. In contrast, ammonia synthesis via electrocatalytic nitrate / nitrite reduction reaction (NO3RR) is more thermodynamically and kinetically favorable, showing superior ammonia yield and Faradaic efficiency. In addition, the NO3RR to NH3 process provides a win-win opportunity for distributed fertilizer synthesis and water nitrogen pollution control using renewable electricity.
[0003] NO3RR is often accompanied by a competing hydrogen evolution reaction (HER) due to the overlap of their reaction potentials and their sensitivity to pH. In general, strong alkaline conditions can accelerate the reaction kinetics of NO3RR and inhibit HER. Therefore, most of the excellent NO3RR to NH3 performances are currently achieved in strong alkaline electrolytes. For example, for copper catalysts, theoretical and experimental studies have verified the proper adsorption of intermediates (such as *NOH), good kinetics, and the inhibition of HER under alkaline conditions, which leads to better NO3RR to NH3 selectivity and activity compared with acidic or neutral conditions. However, the use of strong alkaline electrolytes also brings many disadvantages that are not conducive to practical applications, such as side reactions with ubiquitous CO2, high corrosiveness, and high cost. Therefore, it is very necessary to develop efficient NO3RR to NH3 catalysts suitable for neutral / near-neutral electrolytes.
[0004] Catalytic performance is highly dependent on the local chemical environment around the catalyst. NO3RR to NH3 is accompanied by the generation of OH-. In theory, this process can increase the local pH around the catalytic site and inhibit the competitive HER, thereby enhancing the selectivity and activity of NO3RR to NH3. However, for traditional catalysts, the in-situ generated OH- usually diffuses rapidly into the bulk electrolyte due to the concentration gradient, resulting in a slow increase in local pH and catalytic performance. By increasing the surface roughness of the catalyst, for example by nano-sizing particles or constructing surface microstructures, the diffusion of OH- can be slowed down and the local pH can be enhanced to a certain extent, but this effect is still insufficient under stirring or flow conditions. Therefore, effectively limiting the presence of OH- around the catalytic site to increase the local pH is a critical and challenging issue. Summary of the invention
[0005] In view of the defects of the prior art, the object of the present invention is to provide a carbon nanocage-encapsulated metal nanoparticle catalytic electrode and a preparation method thereof and application in electrocatalytic nitrate reduction.
[0006] To achieve the above purpose, the solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing a carbon nanocage encapsulated metal nanoparticle catalytic electrode, comprising the following steps:
[0008] Step (1), preparation of carbon nanocages: evenly spreading basic magnesium carbonate or magnesium carbonate in a horizontal reaction tube, then placing it in a tubular furnace, raising the temperature of the tubular furnace to a set temperature, then injecting carbon source steam into the reaction tube, then reacting in an inert atmosphere for a period of time, in situ encapsulating carbon on the surface of MgO nanoparticles, and then cooling to room temperature. Finally, the powder collected from the reaction tube is treated with a hydrochloric acid solution to remove the MgO template core, and repeatedly rinsed with deionized water and dried to obtain a hollow carbon nanocage (hNC);
[0009] Step (2), preparation of a carbon nanocage encapsulated metal nanoparticle composite catalyst: placing the hollow carbon nanocage (hNC) obtained in step (1) in a sealed bottle, evacuating the bottle, injecting a solution containing metal ions, stirring the bottle for a period of time, filtering the bottle, freeze-drying the bottle, and washing the bottle three times with deionized water to remove the metal ions attached to the outside of the hollow carbon nanocage (hNC); and then performing a second vacuum drying, performing a reduction reaction at a certain temperature and in a reducing gas flow to obtain a carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) in which metal nanoparticles are encapsulated in a closed or semi-closed manner in a layered carbon nanocage (hNC);
[0010] Step (3), preparation of a catalytic electrode: dispersing the carbon nanocage-encapsulated metal nanoparticle composite catalyst (M@hNC) obtained in step (2) in a mixed solution to obtain a catalyst ink, then dropping the catalyst ink onto a glassy carbon electrode (GCE), and drying it naturally at room temperature to obtain a carbon nanocage-encapsulated metal nanoparticle catalytic electrode.
[0011] Preferably, in step (1): the reaction tube is selected from any one of a quartz tube, a corundum tube and a ceramic tube; the set temperature is 500-1200°C, preferably 670-900°C, and the heating rate is 5-50°C / min, preferably 5-20°C / min; the carbon source steam is selected from one or more of the steam of benzene, methane, acetylene, ethanol and pyridine, preferably benzene and / or pyridine; the injection speed of the carbon source steam into the reaction tube is 10-100 μL / min, Preferably, it is 50-100 μL / min, more preferably, it is 50-80 μL / min; the inert atmosphere is selected from one of argon and nitrogen or a mixture of the two; the reaction time is 5-240 min, preferably 30-120 min; the mass ratio of basic magnesium carbonate or magnesium carbonate to carbon source is (0.1-10): 1; the mass concentration of the hydrochloric acid solution is 0.1-10 mol / L; the specific surface area of the obtained hollow carbon nanocage (hNC) is 500-2000 m 2 / g, preferably 1000-2000m 2 / g, more preferably 1500-2000m 2 / g, and the particle size is 5-200nm, preferably 5-50nm, and more preferably 5-20nm.
[0012] Preferably, in step (2): the vacuum is pumped to 5-50Pa, preferably, the vacuum is pumped to 5-15Pa; the solution containing metal ions is prepared from a metal salt and a solvent, the metal salt is selected from one or more of metal chlorides, nitrates and acetates and / or their hydrates, the solvent is water or ethylene glycol, and the molar concentration of the solution containing metal ions is 0.1-0.5mol / L, preferably 0.3-0.5mol / L; the metal is selected from one or more of Cu, Ni, Co, Fe, Pt and Ru, preferably, the metal is copper or a mixture of copper and any one of Ni, Co, Fe, Pt and Ru. composite; stirring time is 1-3h; in the reduction reaction, the reduction reaction atmosphere is a mixed gas of H2 / Ar (volume ratio 5% / 95%), the flow rate of the mixed gas is 10-100sccm, preferably 30-70sccm, the reduction reaction temperature is 200-240°C, and the reduction reaction time is 0.5-1.5h; in the obtained carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC), the mass percentage of metal particles in the composite catalyst (M@hNC) is 0.5-10%, preferably 0.5-5%, and the particle size is 5-200nm, preferably 5-50nm, and more preferably 5-20nm.
[0013] Preferably, in step (3), the mixed solution is 0.8 ml ultrapure water, 0.2 ml ethanol and 150 μl 5% Nafion solution, the mass concentration of the catalyst ink is 1-10 g / L, preferably 2-6 g / L; the catalyst ink is added dropwise onto a glassy carbon electrode (GCE), the volume of the catalyst ink is 1-5 μl, the mass of the catalyst contained is 5-10 μg, the diameter of the glassy carbon electrode (GCE) is 1-5 mm, and the loading rate of the catalyst on the glassy carbon electrode (GCE) is 0.01-0.50 mg / cm 2 , preferably 0.01-0.25 mg / cm 2 .
[0014] In a second aspect, the present invention also provides a carbon nanocage-encapsulated metal nanoparticle catalytic electrode prepared by the preparation method as described above, which is a catalytic electrode in which the metal nanoparticles are encapsulated in a closed or semi-closed manner in a layered carbon nanocage (hNC) and the carbon nanocage-encapsulated metal nanoparticle composite catalyst (M@hNC) is loaded on a glassy carbon electrode (GCE).
[0015] Preferably, the loading rate of the carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) on the glassy carbon electrode (GCE) is 0.01-0.50 mg / cm 2 , preferably 0.01-0.25 mg / cm 2; The particle size of the carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) is 5-200nm, preferably 5-50nm, and more preferably 5-20nm.
[0016] In a third aspect, the present invention further provides a use of the carbon nanocage-encapsulated metal nanoparticle catalytic electrode as described above in electrocatalytic nitrate reduction.
[0017] Preferably, the carbon nano cage encapsulated metal nanoparticle catalytic electrode is used as the working electrode, a platinum sheet (1 cm×1 cm) is used as the counter electrode, and an Ag / AgCl electrode (3M KCl) is used as the reference electrode to form a three-electrode system; the three-electrode system is placed in a nitrate-containing double-chamber H-type electrolytic cell, the electrolyte is a 0.5M Na2SO4 solution, containing 50mM NaNO3 to provide NO3-, different pH values are adjusted by NaOH or H2SO4 solution, and the cathode chamber and the anode chamber are pretreated with 117 membrane separation, using the Autolab electrochemical workstation, the electrocatalytic nitrate conversion into high value-added ammonia reaction.
[0018] Preferably, the pH value of the electrolyte varies by 7 to 13.
[0019] Preferably, when the applied voltage is -1.5 V vs RHE and the pH value of the electrolyte changes from 7 to 12, the Faradaic efficiency exceeds 80% and the total current density of ammonia production exceeds 80 mA cm -2 .
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The carbon nanocage encapsulated metal nanoparticle catalytic electrode prepared by the present invention is constructed by encapsulating metal nanoparticles in hydrophilic hierarchical carbon nanocages (hNC) to construct a carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) with a closed or semi-closed structure, and the M@hNC catalyst is dripped on a glassy carbon electrode (GCE) to prepare a catalytic electrode for an electrochemical reaction of electrocatalytic nitrate reduction to produce ammonia. The M@hNC catalyst can prevent the escape of OH- ions generated during the electrochemical reaction, thereby forming a self-enhanced local high pH environment around the metal nanoparticles, so that the M@hNC catalyst with a semi-closed environment exhibits excellent NO3RR activity in a neutral electrolyte; the closed structure also effectively inhibits the loss and agglomeration of metal nanoparticles during the NO3RR process, so that the M@hNC catalyst exhibits high activity, high Faraday efficiency and high stability in an alkali-free electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1This is a scanning electron microscope (SEM) image of the carbon nanocage-encapsulated metal nanoparticle composite catalyst (M@hNC) involved in the present invention.
[0023] Figure 2 The schematic diagram of the self-enhanced local alkaline environment of the catalytic electrode of the carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) loaded on the glassy carbon electrode (GCE) during the electrochemical reaction of electrocatalytic nitrate reduction to produce ammonia shows the role of the M@hNC catalyst in NO3RR.
[0024] Figure 3 When the catalytic electrodes prepared in Example 1 of the present invention and the comparative example were subjected to NO3RR, the Faraday efficiency diagram was plotted as the pH value of the electrolyte increased from 7 to 13.
[0025] Figure 4 The total current density chart of ammonia production under different pH values of the electrolyte when the catalytic electrodes prepared in Example 1 of the present invention and the comparative example are subjected to NO3RR.
[0026] Figure 5 When the catalytic electrodes prepared in Examples 1, 2 and 3 of the present invention were subjected to NO3RR, the Faraday efficiency diagram was plotted as the pH value of the electrolyte increased from 7 to 13.
[0027] Figure 6 A chart showing the total current density of ammonia produced under different pH values of the electrolyte when the catalytic electrodes prepared in Examples 1, 2 and 3 of the present invention perform NO3RR. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.
[0029] <Preparation of Carbon Nanocage Encapsulated Metal Nanoparticle Composite Catalyst (M@hNC)>
[0030] The present invention provides a carbon nanocage encapsulated metal nanoparticle composite catalyst, which is a composite catalyst (M@hNC) in which metal nanoparticles are enclosed or semi-enclosed in hierarchical carbon nanocages (hNC). The metal M of the metal nanoparticles includes but is not limited to one or more of Cu, Ni, Co, Fe, Pt and Ru. In the present invention, the metal M of the metal nanoparticles is preferably Cu or a composite of Cu and any one of Ni, Co, Fe, Pt and Ru. In the embodiment of the present invention, Cu is used as an example of the metal M in the M@hNC catalyst to illustrate the technical solution of the present invention.
[0031] The present invention further provides a method for preparing the above-mentioned carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC), comprising the following steps:
[0032] Step (1), preparation of carbon nanocages: using basic magnesium carbonate (or magnesium carbonate) and carbon-containing organic matter such as benzene as precursors, using magnesium oxide nanoparticles generated by in-situ decomposition of basic magnesium carbonate or magnesium carbonate as templates, forming carbon-encapsulated magnesium oxide nanoparticles with a core / shell structure, and then removing the core of the magnesium oxide template by physical and chemical methods to obtain hollow carbon nanocages. Specifically comprising the following steps:
[0033] (1.1) Spread basic magnesium carbonate (or magnesium carbonate) evenly in a horizontal reaction tube and then place it in a tube furnace.
[0034] In this step, the basic magnesium carbonate (or magnesium carbonate) used is an important precursor for making carbon nanocages, which is easy to recycle and reuse, thereby reducing costs.
[0035] In this step, the reaction tube used can be a quartz tube, a corundum tube or a ceramic tube. In the embodiment of the present invention, a quartz tube is used as an example of a reaction tube to illustrate the technical solution of the present invention. The reaction tube filled with basic magnesium carbonate (or magnesium carbonate) powder can be placed in the middle of the tube furnace.
[0036] (1.2) The temperature of the tube furnace is raised to a set temperature, and then carbon source vapor is injected into the reaction tube, followed by a reaction in an inert atmosphere for a period of time to in-situ encapsulate carbon on the surface of the MgO nanoparticles, and then cooled to room temperature.
[0037] In this step, the temperature of the tube furnace is raised to a set temperature of 500-1200°C (preferably 600-1000°C, more preferably 670-900°C) at a heating rate of 5-50°C / min (preferably 5-20°C / min, such as 10°C / min or 15°C / min), and then carbon source steam is injected into the reaction tube through an injection pump at an injection rate of 10-100 μL / min (preferably 50-100 μL / min, more preferably 50-80 μL / min). The carbon source steam includes but is not limited to benzene, methane, acetylene, ethanol or pyridine steam. In the embodiments of the present invention, benzene and pyridine are used as examples of carbon sources to illustrate the technical solution of the present invention. At a set temperature of 500-1200°C (preferably 600-1000°C, more preferably 670-900°C), the carbon source coats the magnesium carbonate nanoparticles and undergoes a pyrolysis reaction, the magnesium carbonate nanoparticles are pyrolyzed into magnesium oxide nanoparticles, the carbon source is pyrolyzed into carbon, and a partial graphitization reaction occurs, so that one or more carbon layers are in situ coated on the surface of the magnesium oxide nanoparticles.
[0038] It should be noted that the carbon nanocages prepared by the preparation method of the present invention using pyridine as a carbon source are nitrogen-doped hierarchical carbon nanocages (hNNC). Compared with the carbon nanocages (hNC) prepared from aromatic hydrocarbons such as benzene, pyridine is relatively more stable at a temperature of 500-1200°C (preferably 600-1000°C, more preferably 670-900°C), and the thermal decomposition rate is slower. The carbon atoms produced by thermal decomposition are rapidly adsorbed and dissolved on the surface of the magnesium carbonate particles, and as the number of dissolved carbon atoms reaches supersaturation, they will precipitate onto the surface of the magnesium carbonate nanoparticles and gradually diffuse from the surface to the entire particle to achieve complete coating. Since the thermal decomposition rate of pyridine is slower, fewer magnesium carbonate template particles, or even a single magnesium carbonate template particle, can be completely deposited and coated, and the formed carbon nanocages have a smaller particle size (particle size of 50-200nm) and a larger specific surface area (specific surface area of 1000-2000m 2 / g), and a closed carbon nanocage is obtained. However, the carbon nanocage prepared from aromatic hydrocarbons such as benzene may simultaneously encapsulate multiple magnesium carbonate nanoparticles due to its poor high temperature stability and fast thermal decomposition rate, resulting in a carbon nanocage with a larger particle size (5-50nm) and a smaller specific surface area (50-1000m 2 / g), and the obtained carbon nanocages may have partial coating phenomenon, and the formed carbon nanocages may have openings (semi-closed carbon nanocages).
[0039] In this step, the injection rate of the carbon source steam into the reaction tube can be 10-100 μL / min, preferably 50-100 μL / min, more preferably 50-80 μL / min, for example 60 μL / min or 70 μL / min; the inert atmosphere used is selected from one or a mixture of argon and nitrogen; the reaction time is 5-240 min, preferably 30-120 min; the mass ratio of basic magnesium carbonate or magnesium carbonate to the carbon source is (0.1-10):1.
[0040] (1.3) Finally, the powder collected from the reaction tube was treated with a hydrochloric acid solution to remove the MgO template core, and then repeatedly rinsed with deionized water and dried to obtain hollow carbon nanocages (hNCs).
[0041] In this step, the mass concentration of the hydrochloric acid solution used can be 0.1-10 mol / L.
[0042] The hollow carbon nanocage (hNC) prepared by the above preparation method includes nitrogen-doped hollow carbon nanocage (hNNC) with a specific surface area of 50-2000m 2 / g, preferably 1000-2000m2 / g, more preferably 1500-2000m 2 / g, and the particle size is 5-200nm, preferably 5-50nm, and more preferably 5-20nm.
[0043] Step (2), preparation of carbon nano cage encapsulated metal nanoparticle composite catalyst:
[0044] (2.1) The hollow carbon nanocage (hNC) obtained in step (1) is placed in a sealed bottle, evacuated, and then a solution containing metal ions is injected and stirred for a period of time.
[0045] In this step, the hollow carbon nanocage (hNC) obtained in the above step (1) is immersed in a solution containing metal ions under vacuum, so that the metal ions are impregnated into the hollow carbon nanocage (hNC) and supported in the hollow carbon nanocage (hNC).
[0046] In this step, the sealed bottle is evacuated to 5-50 Pa, preferably, evacuated to 5-15 Pa, for example, evacuated to about 10 Pa, and the stirring time is 1-3 hours, and the effect of the immersion process is the best.
[0047] According to the technical solution of the present invention, the solution containing metal ions is prepared by metal salt and solvent, wherein the metal salt includes but is not limited to one or more of metal chloride, nitrate and acetate and / or their hydrates, and the metal includes but is not limited to one or more of Cu, Ni, Co, Fe, Pt and Ru. In the present invention, the metal is preferably Cu or a composite of Cu and any one of Ni, Co, Fe, Pt and Ru. In an embodiment of the present invention, the technical solution of the present invention is explained by taking Cu(NO3)2 as an example of metal salt. In the present invention, the solvent is water or ethylene glycol, and the molar concentration of the solution containing metal ions can be 0.1-0.5mol / L, preferably 0.3-0.5mol / L, for example 0.4mol / L.
[0048] (2.2) It was then filtered, freeze-dried, and washed three times with deionized water to remove the metal ions attached to the outside of the hollow carbon nanocages (hNCs).
[0049] In this step, a freeze-drying method is used to freeze the solution containing the carbon nanocage (hNC) nanoparticles loaded with metal ions to below the freezing point (-10°C to -50°C), convert the solution into ice, and then directly convert the solvent component in the ice into steam under a relatively high vacuum (1.3 to 13 Pa) to remove the solvent, thereby achieving the purpose of drying. Compared with conventional drying methods, the carbon nanocage (hNC) nanoparticles loaded with metal ions obtained by freeze-drying can maintain the original porous structure to the maximum extent.
[0050] (2.3) After a second vacuum drying, a reduction reaction is carried out at a certain temperature in a reducing gas flow.
[0051] In this step, the second vacuum drying step can be a common vacuum drying method or a freeze drying method, which is not strictly limited here.
[0052] In this step, the metal ions in the carbon nanocage (hNC) nanoparticles loaded with metal ions obtained in step (2.2) are reduced to metal nanoparticles by a reduction reaction after vacuum drying. In the present invention, the reduction reaction is carried out at a temperature of 200-240° C. in a mixed gas of reducing gas H2 / Ar (volume ratio 5% / 95%) for 0.5-1.5 h. Other reduction methods are also within the scope of protection of the present invention.
[0053] Through the above preparation method, a carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) in which metal nanoparticles are encapsulated in a layered carbon nanocage (hNC) in a closed or semi-closed manner is finally obtained. In the obtained carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC), the mass percentage of metal particles in the composite catalyst (M@hNC) is 0.5-10%, preferably 0.5-5%, and the particle size is 5-200nm, preferably 5-50nm, and more preferably 5-20nm. In the present invention, the metal M of the metal nanoparticles includes but is not limited to one or more of Cu, Ni, Co, Fe, Pt and Ru. In the present invention, the metal M of the metal nanoparticles is preferably Cu or a composite of Cu and any one of Ni, Co, Fe, Pt and Ru.
[0054] The scanning electron microscope (SEM) image of the prepared carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) is shown in Figure 1 shown.
[0055] <Preparation of Carbon Nanocage Encapsulated Metal Nanoparticle Catalytic Electrode>
[0056] The present invention further provides a carbon nanocage-encapsulated metal nanoparticle catalytic electrode, and its preparation method comprises the following steps: dispersing the carbon nanocage-encapsulated metal nanoparticle composite catalyst (M@hNC) as described above in a mixed solution to obtain catalyst ink, and then dropping the catalyst ink onto a glassy carbon electrode (GCE), and naturally drying it at room temperature to obtain the obtained electrode.
[0057] In the above preparation process, the mixed solution used is 0.8 ml ultrapure water, 0.2 ml ethanol and 150 μl 5% Nafion solution, the mass concentration of the catalyst ink is 1-10 g / L, preferably 2-6 g / L; the catalyst ink is added dropwise to the glassy carbon electrode (GCE), the volume of the catalyst ink is 1-5 μl, the mass of the catalyst contained is 5-10 μg, the diameter of the glassy carbon electrode (GCE) is 1-5 mm, and the loading rate of the catalyst on the glassy carbon electrode (GCE) is 0.01-0.50 mg / cm 2 , preferably 0.01-0.25 mg / cm 2 .
[0058] <Application of Carbon Nanocage Encapsulated Metal Nanoparticle Catalytic Electrode in Electrocatalytic Nitrate Reduction>
[0059] The present invention further provides a use of the carbon nanocage-encapsulated metal nanoparticle catalytic electrode as described above in electrocatalytic nitrate reduction.
[0060] According to the technical solution of the present invention, the catalytic electrode used in the present invention is a carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) loaded on a glassy carbon electrode (GCE), wherein the carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) of the present invention is a composite catalyst in which metal nanoparticles are enclosed or semi-enclosed in a layered carbon nanocage (hNC), and according to the different carbon sources of the carbon nanocage, it also includes metal nanoparticles enclosed in a nitrogen-doped layered carbon nanocage (hNNC), the metal M of the metal nanoparticles includes but is not limited to one or more of Cu, Ni, Co, Fe, Pt and Ru, and in the present invention, the metal M of the metal nanoparticles is preferably Cu or a composite of Cu and any one of Ni, Co, Fe, Pt and Ru.
[0061] According to the scheme of the present invention, the present invention adopts metal Cu or metal Cu and any one of Ni, Co, Fe, Pt and Ru as the composite material of the electrocatalytic electrode, because the metal Cu catalyst is the connection point of H*, has excellent hydrogen adsorption and desorption ability, optimizes the reaction kinetics of NO3RR, can improve the hydrogenation step at a more positive potential (≥-0.4V vs.RHE), greatly reduce the overpotential of NO3RR, and on the other hand, need to better inhibit the hydrogen evolution reaction, because high hydrogen coverage tends to be kinetically favorable to hydrogen evolution rather than NO3RR ammonia production, and metal Cu and any one of Ni, Co, Fe, Pt and Ru alloy materials can inhibit water dissociation, adjust the coverage of adsorbed hydrogen (*H), thereby inhibiting undesirable hydrogen evolution reaction, accurately regulate the appropriate amount of adsorbed hydrogen, to meet the specific hydrogenation requirements of NO3RR, improve catalytic activity, and then achieve higher ammonia Faraday efficiency. At the same time, compared with platinum group metals (Ru, Rh, Pd) as metal catalysts, metal Cu catalysts have lower costs and are more conducive to industrial production. In the examples of the present invention, Cu is used as an example of the metal M in the M@hNC catalyst to illustrate the technical solution of the present invention.
[0062] According to the scheme of the present invention, the present invention uses a carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) as a composite material for an electrocatalytic electrode, and constructs a carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) with a closed or semi-closed structure by encapsulating metal nanoparticles in a hydrophilic layered carbon nanocage hNC, and the M@hNC catalyst is dripped onto a glassy carbon electrode (GCE) to prepare a catalytic electrode for the electrochemical reaction of electrocatalytic nitrate reduction to ammonia (NO3RR). The M@hNC catalyst can prevent the escape of OH- ions generated in the NO3RR process, thereby forming a self-enhanced local high pH environment around the metal nanoparticles (a schematic diagram of the self-enhanced local alkaline environment is shown in FIG. Figure 2 As shown in the figure, therefore, it is confirmed by the embodiments of the present invention that the Cu@hNC catalyst with a semi-closed environment exhibits excellent NO3RR activity in a neutral electrolyte (pH 7), and its performance is equivalent to that of the Cu-hNC catalyst with an open environment in a strong alkaline electrolyte. The closed structure also effectively inhibits the loss and agglomeration of metal nanoparticles during the NO3RR process, so that the M@hNC catalyst exhibits high activity, high Faraday efficiency and high stability in an alkali-free electrolyte, providing an economical and sustainable alternative for ammonia synthesis.
[0063] At the same time, the present invention also provides an electrochemical system for electrocatalytic nitrate reduction, in which the carbon nanocage-encapsulated metal nanoparticle catalytic electrode is used as a working electrode, a platinum sheet (1 cm×1 cm) is used as a counter electrode, and an Ag / AgCl electrode (3M KCl) is used as a reference electrode to form a three-electrode system; the three-electrode system is placed in a double-chamber H-type electrolytic cell containing nitrate, the electrolyte is a 0.5M Na2SO4 solution containing 50mM NaNO3 to provide NO3-, different pH values are adjusted by NaOH or H2SO4 solution, and the cathode chamber and the anode chamber are pretreated with 117 membrane separation, using the Autolab electrochemical workstation, the electrocatalytic nitrate conversion into high value-added ammonia reaction. The pH value of the electrolyte changes from 7 to 13.
[0064] The embodiments of the present invention confirm that the electrochemical system for electrocatalytic nitrate reduction using the carbon nanocage encapsulated metal nanoparticle catalytic electrode of the present invention can achieve a Faradaic efficiency of more than 80% and a total current density of ammonia production of more than 80 mA cm when the applied voltage is -1.5 V vs RHE and the pH value of the electrolyte changes from 7 to 12. -2 .
[0065] The present invention is further described below in conjunction with examples, the purpose of which is to better understand the content of the present invention and reflect the essential characteristics of the present invention, so the examples cited should not be regarded as limiting the scope of protection of the present invention. It is also particularly pointed out here that the specific experimental methods and equipment involved in the examples are conventional methods or implemented under the conditions recommended by the manufacturer's instructions unless otherwise specified, and the reagents involved are commercially available unless otherwise specified.
[0066] Embodiment 1:
[0067] A method for preparing a carbon nanocage encapsulated metal nanoparticle catalytic electrode comprises the following steps:
[0068] Step S1: 2 g of basic magnesium carbonate was evenly spread in a horizontal quartz tube with a diameter of 30 mm, which was then placed in a tube furnace; when the furnace temperature was raised to 800 °C at a rate of 10 °C / min, 1.6 mL of benzene was introduced into the quartz tube by a syringe pump within 30 min; the reaction system was then cooled to room temperature in an argon atmosphere; the prepared sample was treated with a 1:1 (volume ratio of concentrated hydrochloric acid to water) hydrochloric acid solution and repeatedly rinsed with deionized water to remove the MgO template to obtain hNC;
[0069] Step S2: 50 mg hNC was placed in a sealed bottle, vacuumed to about 10 Pa, and then 30 mL 0.4 M Cu(NO3)2 solution was quickly injected, followed by magnetic stirring for 2 hours; the sample was filtered, freeze-dried, and washed three times with deionized water to remove Cu(NO3)2 attached to the outside of hNC; after the second vacuum drying, the sample was reduced with 50 sccm H2 / Ar (5% / 95% vol.) gas flow at 220°C for 1 hour to obtain the catalyst (Cu@hNC);
[0070] Step S3: Ultrasonic dispersion of 5 mg of the catalyst (Cu@hNC) in a mixed solution, the mixed solution including 0.8 mL of ultrapure water, 0.2 mL of ethanol and 150 μL of 5% Nafion solution, followed by stirring overnight to obtain a catalyst ink; then, 2 μL of the catalyst ink was dropped onto a glassy carbon electrode (GCE) with a diameter of 3 mm and dried naturally at room temperature.
[0071] The catalyst mass loading on the prepared carbon nanocage encapsulated metal nanoparticle catalytic electrode is 0.12 mg / cm 2 .
[0072] Electrochemical tests were performed in an H-type electrolytic cell with a three-electrode configuration using an Autolab electrochemical workstation. The anode and cathode compartments of the H-type electrolytic cell were pre-treated with 117 membrane. The experiment was carried out at room temperature and pressure, using a three-electrode system, in which the working electrode was the above-mentioned carbon nanocage-encapsulated metal nanoparticle catalytic electrode sample, the reference electrode was an Ag / AgCl electrode (3M KCl), and the counter electrode was a platinum sheet (1cm×1cm). All potential values were converted to the reversible hydrogen electrode scale. The electrolyte was a 0.5M Na2SO4 solution containing 50mM NaNO3 to provide NO3-, and different pH values (7 to 13) were adjusted by NaOH or H2SO4 solution.
[0073] Electrochemical tests were performed in a three-electrode configuration in an H-type electrolytic cell using an Autolab electrochemical workstation. Nitrate reduction reaction experiments were performed in a 10 mL H-type electrolytic cell using a three-electrode system, and the cell was separated by a pretreated proton exchange membrane (Nafion 117). All potentials are referenced to the Ag / AgCl electrode unless otherwise stated. Under stable pH conditions, the potential of Ag / AgCl can be converted to the reversible hydrogen electrode (RHE) scale using the following formula: ERHE = EAg / AgCl + 0.0592 × pH + 0.209. Before each electrochemical test, argon (20 sccm) flowed in the cathode chamber for 15 min and continued to flow throughout the NO3RR experiment. Before the first electrochemical measurement, the working electrode with the catalyst (Cu@hNC) was preconditioned by two potential static cycles at -1.5 V for 0.5 h. The constant current test was carried out at different potentials for 0.5 h and a rotation speed of 300 rpm; the cycle stability test was carried out at -1.5 V and each cycle lasted 0.5 h. All electrochemical results were not iR compensated. The evaporated NH3 in the outflow gas from the cathode chamber was collected using a 0.05M H2SO4 absorption solution. The amount of NH3 in the cathode and anode electrolytes and H2SO4 solutions was detected and quantified, and the total was used to calculate the NH3 yield and Faraday efficiency.
[0074] Embodiment 2:
[0075] The preparation of electrode materials and the method for catalytic reduction of nitrate are the same as those in Example 1, except that the benzene in step S1 is replaced by pyridine.
[0076] Embodiment 3:
[0077] The preparation of electrode materials and the method for catalytic reduction of nitrate are the same as in Example 1, except that 30 mL of 0.4 M Cu(NO3)2 solution and 30 mL of 0.4 M Co(NO3)2 solution are injected in step S2.
[0078] Comparative Example:
[0079] The preparation of electrode materials and the method for catalytic reduction of nitrates are the same as in Example 1, except that step S2 is:
[0080] 20 mg of hNC was ultrasonically dispersed in 50 mL of ethylene glycol (EG), and then 1 mL of 0.4 M Cu(NO3)2 / EG solution and 4 mL of 0.2 M NaOH / EG solution were added in sequence. The mixture was stirred for 4 h, irradiated in a 700 W microwave oven for 40 s, and then allowed to stand for 5 min. After filtration, it was washed with ethanol and water and dried at 70 ° C to obtain open-structured Cu / hNC.
[0081] When the catalytic electrodes obtained in Example 1 and the comparative example were subjected to NO3RR, as the pH increased from 7 to 13, the Faraday efficiency changed as follows: Figure 3 shown.
[0082] When the catalytic electrodes obtained in Example 1 and the comparative example were subjected to NO3RR, under different pH conditions, the total current density of NH3 was as follows: Figure 4 shown.
[0083] from Figure 3 It can be seen that the Cu@hNC catalyst with a semi-closed environment (Example 1) exhibits excellent NO3RR activity in a neutral electrolyte (pH 7), and its performance is equivalent to that of the Cu-hNC catalyst with an open environment in a strong alkaline electrolyte (Comparative Example). Figure 4 It can be seen that the stability of the Cu@hNC catalyst with a semi-closed environment (Example 1) exceeds that of the Cu-hNC catalyst with an open environment (Comparative Example).
[0084] Figure 5 The changes in Faraday efficiency when the catalytic electrodes obtained in Examples 1, 2 and 3 were subjected to NO3RR as the pH increased from 7 to 13 are given.
[0085] Figure 6 The total current density of NH3 under different pH conditions when the catalytic electrodes obtained in Examples 1, 2 and 3 perform NO3RR is given.
[0086] from Figure 5 and Figure 6 It can be seen that the carbon nanocage encapsulated metal nanoparticle catalytic electrode prepared by the present invention has a Faradaic efficiency of more than 80% and a total current density of ammonia production of more than 80 mA cm-2 in an alkali-free electrolyte when the applied voltage is -1.5 V vs RHE and the pH value of the electrolyte changes from 7 to 12. -2 .
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon nanocage encapsulated metal nanoparticle catalytic electrode, characterized in that: The steps include: Step (1), preparation of carbon nanocages: evenly spreading basic magnesium carbonate or magnesium carbonate in a horizontal reaction tube, then placing it in a tubular furnace, raising the temperature of the tubular furnace to a set temperature, then injecting carbon source steam into the reaction tube, then reacting in an inert atmosphere for a period of time, in situ encapsulating carbon on the surface of MgO nanoparticles, and then cooling to room temperature. Finally, the powder collected from the reaction tube is treated with a hydrochloric acid solution to remove the MgO template core, and repeatedly rinsed with deionized water and dried to obtain a hollow carbon nanocage (hNC); Step (2), preparation of a carbon nanocage encapsulated metal nanoparticle composite catalyst: placing the hollow carbon nanocage (hNC) obtained in step (1) in a sealed bottle, evacuating the bottle, injecting a solution containing metal ions, stirring the bottle for a period of time, filtering the bottle, freeze-drying the bottle, and washing the bottle three times with deionized water to remove the metal ions attached to the outside of the hollow carbon nanocage (hNC); and then performing a second vacuum drying, performing a reduction reaction at a certain temperature and in a reducing gas flow to obtain a carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) in which metal nanoparticles are encapsulated in a closed or semi-closed manner in a layered carbon nanocage (hNC); Step (3), preparation of a catalytic electrode: dispersing the carbon nanocage-encapsulated metal nanoparticle composite catalyst (M@hNC) obtained in step (2) in a mixed solution to obtain a catalyst ink, then dropping the catalyst ink onto a glassy carbon electrode (GCE), and drying it naturally at room temperature to obtain a carbon nanocage-encapsulated metal nanoparticle catalytic electrode.
2. The preparation method according to claim 1, characterized in that: In step (1), the reaction tube is selected from any one of a quartz tube, a corundum tube and a ceramic tube; the temperature is set to 500-1200°C, preferably 670-900°C, and the heating rate is 5-50°C / min, preferably 5-20°C / min; the carbon source steam is selected from one or more of the steam of benzene, methane, acetylene, ethanol and pyridine, preferably benzene and / or pyridine; the injection speed of the carbon source steam into the reaction tube is 10-100 μL / min, preferably The reaction rate is 50-100 μL / min, more preferably 50-80 μL / min; the inert atmosphere is selected from one of argon and nitrogen or a mixture of the two; the reaction time is 5-240 min, preferably 30-120 min; the mass ratio of basic magnesium carbonate or magnesium carbonate to carbon source is (0.1-10): 1; the mass concentration of the hydrochloric acid solution is 0.1-10 mol / L; the specific surface area of the obtained hollow carbon nanocage (hNC) is 500-2000 m 2 / g, preferably 1000-2000m 2 / g, more preferably 1500-2000m 2 / g, and the particle size is 5-200nm, preferably 5-50nm, and more preferably 5-20nm.
3. The preparation method according to claim 1, characterized in that: In step (2), the vacuum is pumped to 5-50Pa, preferably, the vacuum is pumped to 5-15Pa; the solution containing metal ions is prepared from a metal salt and a solvent, the metal salt is selected from one or more of metal chlorides, nitrates and acetates and / or their hydrates, the solvent is water or ethylene glycol, and the molar concentration of the solution containing metal ions is 0.1-0.5mol / L, preferably 0.3-0.5mol / L; the metal is selected from one or more of Cu, Ni, Co, Fe, Pt and Ru, preferably, the metal is copper or a composite of copper and any one of Ni, Co, Fe, Pt and Ru. ; The stirring time is 1-3h; in the reduction reaction, the atmosphere of the reduction reaction is a mixed gas of H2 / Ar (volume ratio 5% / 95%), the flow rate of the mixed gas is 10-100sccm, preferably 30-70sccm, the temperature of the reduction reaction is 200-240°C, and the reduction reaction time is 0.5-1.5h; in the obtained carbon nanocage-encapsulated metal nanoparticle composite catalyst (M@hNC), the mass percentage of metal particles in the composite catalyst (M@hNC) is 0.5-10%, preferably 0.5-5%, and the particle size is 5-200nm, preferably 5-50nm, and more preferably 5-20nm.
4. The preparation method according to claim 1, characterized in that: In step (3), the mixed solution is 0.8 ml ultrapure water, 0.2 ml ethanol and 150 μl 5% Nafion solution, the mass concentration of the catalyst ink is 1-10 g / L, preferably 2-6 g / L; the catalyst ink is added dropwise onto a glassy carbon electrode (GCE), the volume of the catalyst ink is 1-5 μl, the mass of the catalyst contained is 5-10 μg, the diameter of the glassy carbon electrode (GCE) is 1-5 mm, and the loading rate of the catalyst on the glassy carbon electrode (GCE) is 0.01-0.50 mg / cm 2 , preferably 0.01-0.25 mg / cm 2 .
5. A carbon nanocage encapsulated metal nanoparticle catalytic electrode prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The invention discloses a catalytic electrode in which metal nanoparticles are encapsulated in a hierarchical carbon nanocage (hNC) in a closed or semi-closed manner, and a carbon nanocage-encapsulated metal nanoparticle composite catalyst (M@hNC) is supported on a glassy carbon electrode (GCE).
6. The carbon nanocage encapsulated metal nanoparticle catalytic electrode according to claim 5, characterized in that: The loading rate of carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) loaded on glassy carbon electrode (GCE) is 0.01-0.50 mg / cm 2 , preferably 0.01-0.25 mg / cm 2 ; The particle size of the carbon nanocage encapsulated metal nanoparticle composite catalyst (M@hNC) is 5-200nm, preferably 5-50nm, and more preferably 5-20nm.
7. Use of the carbon nanocage-encapsulated metal nanoparticle catalytic electrode as claimed in claim 5 or 6 in electrocatalytic nitrate reduction.
8. The use according to claim 7, characterized in that: The carbon nanocage-encapsulated metal nanoparticle catalytic electrode is used as a working electrode, a platinum sheet (1 cm×1 cm) is used as a counter electrode, and an Ag / AgCl electrode (3M KCl) is used as a reference electrode to form a three-electrode system; the three-electrode system is placed in a nitrate-containing double-chamber H-type electrolytic cell, the electrolyte is a 0.5M Na2SO4 solution containing 50mM NaNO3 to provide NO3-, different pH values are adjusted by NaOH or H2SO4 solution, and the cathode chamber and the anode chamber are pretreated with 117 membrane separation, using the Autolab electrochemical workstation, the electrocatalytic nitrate conversion into high value-added ammonia reaction.
9. The use according to claim 8, characterized in that: The pH value of the electrolyte varies from 7 to 13.
10. The use according to claim 9, characterized in that: At an applied voltage of -1.5 V vs RHE, the Faradaic efficiency exceeded 80% when the pH value of the electrolyte varied from 7 to 12, and the total current density for ammonia production exceeded 80 mA cm -2 .